LINGUISTIC VARIETY AND CHARACTER DEVELOPMENT OF MULTICULTURAL EDUCATION’S PERSPECTIVE - Simon Sabon Ola (International Conference on Languages and Arts, 2014)
This paper discusses about character building, knowing of language and multicultural education. The characters are not able to be developed through slogans, rhetoric, and lectures, but through natural activities which naturally reveal the attitudes, values and characters. One of the activities referred to is the use of kind of languages in society. The discourse about society cannot be separated from multiculturalism. Related with the rights and the existence of native speakers of each language, it is necessary to address the perspectives of multiculturalism differences in social and cultural interaction. Interaction process is allowing the formation of norms and values that lead to the bulding of character. Based on the scrutiny of the language varieties with different characteristics, can be identified a number of characters that can be grown and developed from the varieties of language. The character is identified through language diversity, the diversity of the repertoire, the mother language awareness, dynamism of diglossia, the characteristic choice of language, the role of Indonesian in the perspective of multiculturalism. The characters include democratic, respectful, caring social, religious, national spirit and patriotism. Thus, the varieties of languages can be a medium of education and building character within multiculturalism framework. Keywords: multilingualism, character, multiculturalism